THE INFLUENCE OF WORK DISCIPLINE AND COOPERATION ON EMPLOYEE PERFORMANCE AT THE DIRECTORATE GENERAL OF CONSUMER PROTECTION AND TRADE ORDER, MINISTRY OF HOME AFFAIRS - Herdjuno Wahyu Moertyanto; Zulkifli Rangkuti; Hadi Purnomo (Jurnal Manajemen Bisnis Dan Organisasi, 2026)
This study aims to analyze the influence of work discipline and cooperation on employee performance at the Directorate General of Consumer Protection and Trade Order, Ministry of Home Affairs. The problem in this study is based on the ongoing obstacles in achieving employee work targets, which are influenced by the level of discipline and the effectiveness of cooperation between employees in carrying out their duties. This study uses a quantitative method with an associative approach. Data collection techniques were carried out by distributing questionnaires to employees who served as research respondents. Data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results of the study indicate that work discipline has a positive and significant effect on employee performance, and cooperation also has a positive and significant effect on employee performance. Simultaneously, work discipline and cooperation contribute significantly to improving employee performance. The implications of this study indicate that improving discipline through compliance with work rules and strengthening effective teamwork can support the creation of more optimal employee performance in achieving organizational goals.